Factors Influencing Consumer Purchase Intention Of Dietary Supplement Products In Penang Island - Ooi, Say Keat (2009)
The purpose of this crosssectional study is to examine the factors influencing consumer purchase intention of dietary supplement products in Penang based on Theory of Planned Behaviour (TPB). Tujuan kajian ini adalah untuk mengkaji faktor-faktor yang mempengaruhi pembelian suplemen pemakanan di kalangan pengguna di negeri Pulau Pinang berdasarkan model Theory of Planned Behaviour (TPB).